Polytope Projects - Iordache, Octavian (CRC Press, 2014)
How do you know what works and what doesn't? This book contains case studies highlighting the power of polytope projects for complex problem solving. Any sort of combinational problem characterized by a large variety of possibly complex constructions and deconstructions based on simple building blocks can be studied in a similar way. Although the majority of case studies are related to chemistry, the method is general and equally applicable to other fields for engineering or science.